2016
DOI: 10.1039/c5ce02335a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flux treatment on morphology of single-crystalline BaNbO2N particles

Abstract: Single crystalline BaNbO2N particles with crystal habits were obtained by appropriate flux treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…These results are similar to the crystallinity trend observed in the case of the BaNbO 3 when varying the Nb amount, implying that the crystallinity of BaNbO 3 determines that of BaNbO 2 N. The improved crystallinity of BaNbO 2 N was comparable to that of highly crystalline BaNbO 2 N obtained by a flux-assisted synthesis in our previous study. 10,13 Therefore, it is clear that synthesis using perovskite-type BaNbO 3 is an effective means of obtaining highly crystalline BaNbO 2 N by solid-state reaction. The structural transition of high crystalline BaNbO 3 (2.0Nb) during nitridation over 20 h was investigated, and the results are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to the crystallinity trend observed in the case of the BaNbO 3 when varying the Nb amount, implying that the crystallinity of BaNbO 3 determines that of BaNbO 2 N. The improved crystallinity of BaNbO 2 N was comparable to that of highly crystalline BaNbO 2 N obtained by a flux-assisted synthesis in our previous study. 10,13 Therefore, it is clear that synthesis using perovskite-type BaNbO 3 is an effective means of obtaining highly crystalline BaNbO 2 N by solid-state reaction. The structural transition of high crystalline BaNbO 3 (2.0Nb) during nitridation over 20 h was investigated, and the results are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…In these compounds, the substitution of Nb at B sites lowers the band gap energy to well below that of Ta, owing to the relatively high electronegativity of Nb. SrNbO 2 N and BaNbO 2 N photocatalysts exhibit the longest light absorption edges of 700 and 740 nm, respectively, suggesting that the use of these materials may result in high STH conversion efficiencies. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kodera et al. reported that BaNbO 2 N crystals with different morphologies and crystallinities can be prepared using a range of alkali halide fluxes, and they demonstrated that the types of cations present in the flux play an important role in determining the shapes of the resulting BaNbO 2 N crystals . It is noted that the morphology and crystallinity of crystals are also determined by the synthetic conditions employed, as these can influence the solubility of the solutes; examples include the precursor-to-flux molar ratio, the operating temperature, and the nitridation time. The optimization of these conditions along with the flux is therefore of particular importance.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the skeletal and edgy morphology has higher CoOx catalyst dispersion on the LaTiO 2 N electrode contained unsaturated bonds, thereby improving the photocatalytic O 2 evolution. Moreover, Kodera et al demonstrated that flux treatment on BaNbO 2 N photoelectrodes greatly influenced the morphological natures [83]. Prior to flux action, the BaNbO 2 N morphological features were uncertain, with an accumulation of particle sizes varied from a few 10' s nm to 100 s nm.…”
Section: (Oxy)nitrides Based Materialsmentioning
confidence: 99%